An analytical approach to reinforced earth system - Eygören, Fikret. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
In this study, Reinforced Earth Structures are investigated by using various techniques. Inltially the system is handled as a slope stability problem and multi-criterion analysis method is employed to find out the allowable tensile and shear forces for the reinforcing bars. A computer program, which evaluates the forces mobilized in the bars and estimates the safety factor, is prepared, In the second part of the study, reinforced earth systems are analyzed by the Finite Element Method. For this purpose, the system is considered as a composite material and necessary formulations are derived. In the analysis, the hyperbolic stress-strain parameters are utilized to take into account the real behaviour of the soil. A finite element computer program, having various capacities is also developed in this study.
Keywords: Soil stabilization.; Strains and stresses.; Finite element method.